Estudio De Amenazas Y Vulnerabilidades En La Infraestructura Tecnológica Del Centro Tecnológico Disgraptec De La Ciudad De Montalvo - Cuvi Alulema, Lilia Inés (2018)
The system of endowment and deployment of the Internet service, now known as broadband, is often subject to vulnerabilities due to unauthorized intrusions; In Ecuador there is a constant proliferation of small Internet Service Providers (ISPs), which are part of establishing the greatest amount of coverage through the aggregation of subscribers in different geographical areas of the territory established for operations. However, it is detected that a certain number of these companies do not have the necessary mechanisms to control and monitor the possible incidents, as well as the different anomalies that develop in the scenario of operation, escalation and control of threats. Therefore, a revision of the methods and techniques of unauthorized access to the previously defined service will be carried out; This will also provide a series of possible solutions to the different error scenarios in order to prevent and avoid any type of inconvenience that compromises the security of the network and directly the technological infrastructure of Disgraptec.